1999
DOI: 10.1021/ic980973o
|View full text |Cite
|
Sign up to set email alerts
|

Technetium Complexes of a Hydrazinonicotinamide-Conjugated Cyclic Peptide and 2-Hydrazinopyridine:  Synthesis and Characterization

Abstract: Ternary ligand technetium complexes of a hydrazinonicotinamide-conjugated cyclic peptide (HYNICtide: cyclo(D-Val-NMeArg-Gly-Asp-Mamb(5-(6-(6-hydrazinonicotinamido)hexanamide)))) and 2-hydrazinopyridine (HYPY) were prepared and characterized by various spectroscopic methods. The HPLC concordance experiments for (99m)Tc and (99)Tc analogues show clearly that the same complexes are prepared on the no-carrier-added ((99m)Tc) and the carrier-added ((99)Tc) levels. Using a chirality experiment, it was demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 41 publications
4
66
0
Order By: Relevance
“…Using a chirality experiment, it has been demonstrated that the presence of two isomeric forms is due to the resolution of diastereomers resulting from a combination of the chiral technetium chelate and chiral centers in the cyclic peptide. It was also found that the two diastereomers of RP444 possess equal biological activity [46]. The chemical composition of these ternary ligand 99m Tc complexes has been determined to be 1:1:1:1 for Tc:HYNIC:L:tricine through a series of mixed-ligand experiments [42], and was confirmed by LC-MS at both the tracer level and the macroscopic level [46,54].…”
Section: Ternary Ligand Technetium Complexesmentioning
confidence: 87%
See 3 more Smart Citations
“…Using a chirality experiment, it has been demonstrated that the presence of two isomeric forms is due to the resolution of diastereomers resulting from a combination of the chiral technetium chelate and chiral centers in the cyclic peptide. It was also found that the two diastereomers of RP444 possess equal biological activity [46]. The chemical composition of these ternary ligand 99m Tc complexes has been determined to be 1:1:1:1 for Tc:HYNIC:L:tricine through a series of mixed-ligand experiments [42], and was confirmed by LC-MS at both the tracer level and the macroscopic level [46,54].…”
Section: Ternary Ligand Technetium Complexesmentioning
confidence: 87%
“…Since then, the HYNIC technology has successfully been used for the 99m Tc-labeling of antibodies [3][4][5][6][7][8] and small biomolecules (BMs), including chemotactic peptides [9][10][11][12][13][14][15][16][17][18], somatostatin analogs [19][20][21][22][23][24][25],"stealth" liposomes [26,27], antisense oligonucleotides [28][29][30][31], a folate receptor ligand [32], and polypeptides [32][33][34]. A ternary ligand system (HYNIC, tricine, and trisodium triphenylphosphine-3,3¢,3≤-trisulfonate, TPPTS) has been used for the 99m Tc-labeling of chemotactic peptides [35] and leukotriene B 4 (LTB 4 ) receptor antagonists [36][37][38][39] for imaging infection and inflammation, integrin a v b 3 receptor antagonists for tumor imaging [40], and a glycoprotein IIb/IIIa (GPIIb/IIIa) receptor antagonist for imaging thrombosis [41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the last decade, we have been using ternary ligand systems (HYNIC, tricine, water soluble phosphine or pyridine analog) for 99m Tc-labeling of small biomolecules, including chemotactic peptides [40] and LTB 4 antagonists [41,42] for imaging infection/inflammation, integrin α v β 3 antagonists for tumor imaging [27][28][29][30], and a GPIIb/IIIa antagonist for imaging thrombosis [43][44][45][46]. Regardless of the biomolecule, the Tc:HYNIC:L:tricine ratio in [ 99m Tc(HYNIC-biomolecule)(tricine)(L)] always remains 1:1:1:1 as demonstrated via mixed ligand experiments at the tracer level [43,44], and has been further confirmed by the LC-MS data of [ 99m Tc(HYNIC-biomolecule)(tricine)(L)] (L = TPPTS and ISONIC) at both macroscopic and tracer levels [47,48]. Based these results, it is reasonable to believe that ternary ligand complexes [ 99m Tc(HYNIC-tetramer)(tricine)(L)] (L = ISONIC and PDA) contain one HYNIC-tetramer, one tricine, and one monodentate ISONIC or PDA.…”
Section: Radiochemistrymentioning
confidence: 73%